Nghiên cứu xác định vết chì (Pb), indi (In) và cadimi (Cd) bằng phương pháp von-ampe hòa tan anot sử dụng điện cực paste ống nanocacbon biến tính bằng Bi2O3 - Thu Phương, Nguyễn Thị; Giản, Trịnh Xuân (Vietnam Journal of Chemistry, 2014)
This paper reports the use of Bi2O3-modified carbon nanotubes paste electrode (Bi2O3-CNTPE) for trace lead (Pb), cadmium (Cd) and indium (In) determination by differential pulse anodic stripping voltammetry (DP-ASV). The stripping peak current (Ip) has a linear relationship with concentration in the range of Pb(II), In(III) and Cd(II) are 1.21×10-8 M to 4.83×10-8 M, 5.22×10-8 M to 12.17×10-8 M, 2.23×10-8 M to 8.93×10-8 M, respectively, with a deposition time of 60 s at deposition potential of -1.2 V, in 0.1 M acetate buffer (pH = 4.5) and 0.1 M KBr. The 3σ detection limit (n = 10) of Pb, in and Cd is 0.83×10-9 M, 6.47×10-9 M, 1.38×10-9 M, respectively. The electrode was applied to determination of Pb(II), In(III) and Cd(II) in water sample. Keywords: Stripping Voltammetry, Bi2O3-CNTPE, lead, indium, cadmium